Efficacy evaluation of Buyang Huanwu Decoction in the treatment of ischemic stroke in the recovery period: A systematic review of randomized controlled trials - Wang, Raoqiong; Ren, Junhao; Li, Shuangyang; Bai, Xue; Guo, Wubin; Yang, Sijin; Wu, Qibiao; Zhang, Wei (Frontiers in Pharmacology, 2022)
Background and purpose: Buyang Huanwu decoction (BYHWD) is widely used in the treatment of ischemic stroke in the recovery period, and many clinical trials have been reported, but its clinical efficacy and safety have not been fully evaluated. In this study, we conducted a systematic review and meta-analysis to evaluate the clinical efficacy and safety of BYHWD in the recovery period. Materials and methods: Eight databases, including CNKI, Wanfang Database, VIP Database, China Biomedical Literature Database, PubMed, Cochrane Library, EMBASE, and Web of Science, were searched from the establishment of the database to April 13, 2022. We selected all eligible randomized controlled trials of BYHWD in the treatment of ischemic stroke during the recovery period. Systematic review and meta-analysis were conducted in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. The National Institutes of Health Stroke Score (NIHSS) was the primary outcome, and the Chinese Stroke Scale (CSS), activities of daily living (ADL), and adverse drug reaction (ADR) were the secondary outcomes. Results: A total of 39 randomized controlled trials were included, and 3683 patients in the recovery period of ischemic stroke were recruited. Compared with conventional treatment alone, BYHWD combined with conventional treatment significantly decreased the NIHSS score (MD=-1.44, 95% CI: -1.75, -1.12, p<0.00001), the CSS score (MD=-1.18, 95% CI: -2.02, -0.34, p=0.006), improved the ADL (MD=4.33, 95% CI: 3.06, 5.61, p<0.00001), and did not increase the adverse reactions of patients (OR=0.88, 95% CI: 0.48, 1.61, p=0.67). Conclusion: BYHWD is an effective and safe therapy for the recovery of ischemic stroke. To further determine the efficacy and safety of BYHWD in the treatment of ischemic stroke in the recovery period, more high-quality, multicenter, and prospective RCTs are needed.